Introducing SentiMag in a rural setting: a 5‐year experience. Issue 11 (26th July 2021) - Sreedhar, Sharmaine; Maloney, Jay; Hudson, Steven
Abstract: Background: The Sentimag device is a probe that contains a sensitive magnetometer which detects either an implantable magnetic marker (MagSeed) or an infectable superparamagnetic ironoxide nanoparticle tracer (MagTrace). MagSeed is used to localise impalpable breast lesions; MagTrace is used to identify sentinel lymph nodes. In Australasia, Sentinel lymph node (SLN) biopsy, using radioactive colloid injection, is a mainstay of prognostication in breast surgery in patients with a clinically negative axilla. In addition, radioactive seeds or hookwires have been used to detect impalpable breast lesions. Gisborne Hospital has been using the SentiMag device since June 2016 to both identify sentinel lymph nodes (Magtrace) and impalpable tumours (Magseed). This study gives perspective over more than 5 years on how this new technology can benefit patients and clinicians in the rural setting. Methods: Patient data had been collected by the operative surgeon prospectively and corroborated with the coding department. Consecutive cases performed by a single surgeon were included in this study. Inclusion criteria were: (1) any patient who needed localisation of an impalpable breast lesion; (2) any patient who needed a sentinel lymph node biopsy; (3) cases were collected from January 2013 with the large majority of cases were collected between January 2015 and Jan 2020. Comparisons were made between patients with different localisation methods. Basic demographics were collected at the time of the surgery and outcomes then recorded. Staging, lymph node status, lymph node detection rates and complications were collected. Mode of tumour and sentinel node location was recorded. Financial data was collected from administrative staff via receipts and invoices of purchases to the hospital. Results: Of the 125 patients included in this study: 23 underwent magnetic seed insertion; 15 underwent a hookwire insertion; 45 cases used MagTrace injection; 71 cases used radioactive colloid injection. There was a significantly higher detection rate of two or more sentinel nodes in the SentiMag group. (91% vs. 71.8%, p = 0.01). Neither complication rates, nor cancer detection rates were significantly different. Eighty‐four (67.2%) cases did not require tumour location. Conclusion: SentiMag is safe to use in a rural setting. Using the SentiMag system can simplify care for patients and surgeons and was shown to be cost effective in our hospital. Abstract : Sentinel lymph node biopsy has now become the mainstay of prognostication in breast surgery in patient with a clinically negative axilla. SentiMag, as an alternative to traditional means, likely has patient centred and financial advantage in the rural setting.